High-dose insulin therapy for neurogenic-stunned myocardium after stroke. (21st November 2012) - Devos, Justine; Peeters, André; Wittebole, Xavier; Hantson, Philippe
Abstract : A 44-year-old woman with a history of complicated type 2 diabetes mellitus presented with a diagnosis of right-hemispheric ischaemic stroke. She developed acute respiratory distress with radiological evidence of pulmonary oedema. The ECG showed poorly significant ST-segment changes, with a minimal increase of cardiac biomarkers. Echocardiography showed a severely depressed left ventricular function, with also low values of cardiac output at invasive monitoring. The possibility of neurogenic-stunned myocardium was discussed and a metabolic resuscitation with high-dose insulin was proposed. An intravenous bolus of 80 units of insulin (0.72 IU/kg) was followed by a continuous infusion at the rate of 160 IU/h (1.45 IU/kg/h). The treatment led to a rapid and sustained improvement of the haemodynamic condition and was well tolerated. In comparison with dobutamine, insulin had significant inotropic effects without tachycardia. The patient unfortunately died on day 35, from respiratory complications after poor neurological recovery.